1999
DOI: 10.1523/jneurosci.19-04-01165.1999
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Calmodulin and α-Actinin with the NR1 Subunit Modulate Ca2+-Dependent Inactivation of NMDA Receptors

Abstract: Glutamate receptors are associated with various regulatory and cytoskeletal proteins. However, an understanding of the functional significance of these interactions is still rudimentary. Studies in hippocampal neurons suggest that such interactions may be involved in calcium-induced reduction in the open probability of NMDA receptors (inactivation). Thus we examined the role of the intracellular domains of the NR1 subunit and two of its binding partners, calmodulin and alpha-actinin, on this process using NR1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
288
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(312 citation statements)
references
References 43 publications
23
288
0
1
Order By: Relevance
“…An alternative explanation is that the C-terminal domain has different configurations, which depend on its dynamic interactions with the cytoskeleton. In support of this intriguing possibility, it has been shown that the binding of NR1 to ␣-actinin is displaced by calmodulin (Wyszynski et al, 1997), a process that might explain the calcium-dependent inactivation of NMDA receptors (Ehlers et al, 1996;Zhang et al, 1998;Krupp et al, 1999).…”
Section: Subsynaptic Organization Of Glutamate Receptorsmentioning
confidence: 95%
“…An alternative explanation is that the C-terminal domain has different configurations, which depend on its dynamic interactions with the cytoskeleton. In support of this intriguing possibility, it has been shown that the binding of NR1 to ␣-actinin is displaced by calmodulin (Wyszynski et al, 1997), a process that might explain the calcium-dependent inactivation of NMDA receptors (Ehlers et al, 1996;Zhang et al, 1998;Krupp et al, 1999).…”
Section: Subsynaptic Organization Of Glutamate Receptorsmentioning
confidence: 95%
“…Dimer formation is required for its normal function as a cross-linker of the actin cytoskeleton 111 (Figure 2). In addition to binding to actin filaments, actinins interact with membrane receptors [112][113][114][115] However, the expression and function of Villin 1 in neurons is currently unknown.…”
Section: Actin Cross-linking Proteinsmentioning
confidence: 99%
“…Many mechanisms have been proposed to account for the mediation of the inactivation of NMDARs, including glycine-dependent desensitization, glycine-independent desensitization [5,6], Ca 2+ -dependent inactivation [7][8][9] and surface membrane receptors internalization [10]. Activation of NMDARs that have been pre-equilibrated with glycine produces a peak current, which decays or desensitizes to a steady-state level at high concentrations of NMDA.…”
Section: Citationmentioning
confidence: 99%